Cost-benefit analysis of Lettuce (Lactuca sativa) cultivated in hydroponic farms in Leyte - Abieras, Elmo Santi Yuan D.; Acedera, Angelica Rose S.; Baylon, Rienzee D.
The province of Leyte is challenged with low farm/labor productivity and urbanization. As the demand for urbanization increases, agricultural lands were repurpose to meet the rising demand for residential ad commercial lands. To address these challenges, hydroponic farming techniques were introduced as an alternative solution in the locale. Moreover, among all crops, lettuce is the most planted due to its high value. To determine if hydroponic lettuce farming is a cost-efficient solution, there is a need to assess its long-term sustainability. Nevertheless, there is no available study concerning the economic viability of hydroponic lettuce farming in the locale parameters. This study aimed to conduct a cost-benefit analysis on the hydroponic lettuce farms in Leyte, mainly to assess its profitability and sustainability, with Net Present Value (NPV), Benefit Cost Ration (BCR), Internal Rate of Return (IRR), Payback Period (PP), and Break-Even Point (BEP) as criteria. In the conceptual framework, the benefits should outweigh the costs while taking into accunt the socioeconomic factors and the farm characteristics of the hydroponics lettuce farms that affect both the benefits and costs. The data in the study was acquired from all five (5) hydroponics lettuce operators in the research locale. Results show a positive NPV, a BCR of greater than 1, an IRR of 7%, a payback period of 5.65 years, and a breakeven point of 7,145 which indicates that the lettuce hydroponic farming in Leyte is financially viable and profitable. However, there are production-challenges that constraints hydroponics lettuce farms from operating at their maximum capabilities including weather conditions, plant disease, and pests.